User participation: what can be learned from the information systems domain?. (18th November 2019) - Engvall, Tove
Abstract : Purpose: Many records professionals are involved in the design and development of recordkeeping systems. To design recordkeeping systems that meet user needs, their perspectives have to be included in the design process. The purpose of this paper is to explore what can be learned from the domain of information systems (IS) regarding user participation in design, and then to reflect on what related to the recordkeeping dimension should be further considered. Design/methodology/approach: The study is based on a review of literature in the IS development field about user participation. Findings: Analysing how users participate in IS development reveals several aspects of interest for records professionals. There are different approaches to, purposes of and driving values in user participation, which should be transparent. For user participation to be successful, an infrastructure has to be in place. The idea of user participation may be a way to include the secondary values of records in the near term, but it may also challenge traditional roles. New issues, such as the archivist's role as a trusted third party, should be analysed further. Originality/value: This study uses knowledge from the information system field to acquire new knowledge about user participation in design, and relate it to the recordkeeping domain. This study addresses issues surrounding user participation, which has been indicated as an area in need of further development in archives and information science.